Explicit evidence of an implicit contract - Andrew T. Young; Daniel Levy (Bar-Ilan University, Department of Economics, 2013)
We thank three anonymous referees for thoughtful comments and suggestions which we found very constructive and helpful. We are particularly grateful to the editor, Al Klevorick, for his advice and painstaking guidance through the multiple revision process. We thank Robert Barsky, Susanto Basu, Benny Bental, Mark Bergen, Steve Cecchetti, Robert Chirinko, Alex Cukierman, Leif Danziger, Stanley Fischer, Ben Friedman, Zvi Hercowitz, Arye Hillman, Mark Hooker, Simon Gächter, Robert Gordon, Anil Kashyap, Robert King, Pete Klenow, Ed Knotek, Saul Lach, Jon Moen, Walter Oi, Will Roberds, Christina Romer, David Romer, Julio Rotemberg, Paul Rubin, Rob Saur, Matthew Shapiro, Avichai Snir, Robert Solow, Peter Temin, Ken West, Jon Willis, Janet Yellen, and Mor Zahavi for providing useful comments and suggestions on earlier versions of the paper. We thank also the seminar participants at Bar-Ilan University, Ben-Gurion University, European Central Bank, Emory University, University of Haifa, Hebrew University, ISET, University of Michigan, NBER, and Tel-Aviv University, as well as the participants of the 2008 Annual Conference of the European Association of Law and Economics at the University of Haifa for suggestions and advice. We also thank the Coca-Cola Company Archive employees and especially Phil Mooney, the Coca-Cola Company Historian and the Coca-Cola Company Archive Director, for helping us locate many of the materials used for this project and for patiently answering our questions, and Virginia Cain and Kathy Shoemaker, Emory University Archivists of the Special Collections, for helping us with the papers and correspondence material contained in the Robert W. Woodruff Collection at the Emory University Special Collection Library. Daniel Levy acknowledges financial support from the University Research Committee at Emory University and from Adar Foundation at the Department of Economics at Bar-Ilan University, and research assistance of Eleana Aguilar, Xia Liu, and the late Yihong Xia. Some parts of the manuscript were written at the Monetary Policy Research Division of the European Central Bank in Frankfurt, where Daniel Levy was a visiting scholar. He gratefully acknowledges the Bank's hospitality and research support. All errors are ours.
Keywords: E12; E31; K00; K12; K22; K23; L14; L16; L66; M21; M31; N80; A14; 330; Implicit Contract; Explicit Contract; Invisible Handshake; Customer Market; Long-Term Relationship; Price Rigidity; Sticky Prices; Price Adjustment; Quality Rigidity; Quality Adjustment; Nickel Coke; Coca-Cola; Secret Formula; Real Thing